INT toxicity over natural bacterial assemblages from surface oligotrophic waters : implications for the assessment of respiratory activity - Banos, I.; Montero, M. F.; /Benavides, Mar; Aristegui, J. (2020)
Plankton community respiration (R) is a major component of the carbon flux in aquatic ecosystems. However, current methods to measure actual respiration from oxygen consumption at relevant spatial scales are not sensitive enough in oligotrophic environments where respiration rates are very low. To overcome this drawback, more sensitive indirect enzymatic approaches are commonly used as R proxies. The in vivo electron transport system (ETSvivo) assay, which measures the reduction of (2-(4-iodophenyl)-3-(4-nitrophenyl)-5-phenyl tetrazolium chloride salt, INT) to INT-formazan in the presence of natural substrate levels, was recently proposed as an indirect reliable estimation of R for natural plankton communities. However, under in vivo conditions, formazan salts could be toxic to the cells. Here, we test the toxicity of 0.2 mM of final INT concentration, widely used for ETSvivoassays, on natural bacterial assemblages collected in coastal and oceanic waters off Gran Canaria (Canary Islands, subtropical North Atlantic), in eight independent experiments. After 0.5 h of incubation, a significant but variable decline in cell viability (14-49%) was observed in all samples inoculated with INT. Moreover, INT also inhibited leucine uptake in less than 90 min of incubation. In the light of these results, we argue that enzymatic respiratory rates obtained with the ETSvivomethod need to be interpreted with caution to derive R in oceanic regions where bacteria largely contribute to community respiration. Moreover, the variable toxicity on bacterial assemblages observed in our experiments questions the use of a single R/ETSvivorelationship as a universal proxy for regional studies.